Multi-Scale Tolerance Mechanisms of Xanthium strumarium L. Under Lead Stress and Its Application in Phytoremediation - Shilin Xu; Xiaofang Wang; Zichen Meng; Pingyao Cheng; Wei Li; You Zhou; Yongsheng Li (Plants)
Heavy metal pollution poses a global environmental challenge, with lead (Pb) being particularly concerning due to its persistence and toxicity. This study investigated Xanthium strumarium L. from China’s Yellow River Sanmenxia section through hydroponic experiments (0–600 mg/L Pb2+, 1–11 d exposure) to elucidate its Pb2+ response mechanisms. Integrated analyses (EDX, FTIR, thermogravimetry, hyperspectral imaging) revealed a three-phase sequestration strategy: the roots immobilized 88.55% of Pb through pectin carboxyl de-esterification and lignin–Pb complexation, while the stems and leaves retained <11.14% and <0.31%, respectively. A critical threshold (300 mg/L) triggered nonlinear Pb accumulation escalation. Thermogravimetric analysis demonstrated enhanced cell wall stability under Pb stress (66.7% residual carbon increase at 600 mg/L). Hyperspectral features (1670 nm band intensity) effectively tracked physiological stress dynamics. The findings establish X. strumarium’s superior suitability for root-based immobilization rather than phytoextraction in Pb-contaminated sites, with its low translocation efficiency minimizing ecological risks. The identified concentration threshold and spectral biomarkers provide multi-scale insights for optimizing in situ phytostabilization strategies, advancing both theoretical understandings and practical applications in heavy metal remediation.